2007
DOI: 10.1016/j.pbb.2006.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Progestins influence motivation, reward, conditioning, stress, and/or response to drugs of abuse

Abstract: Progesterone (pregn-4-ene-3,20-dione; P) and its metabolite 5α-pregnan-3α-ol-20-one (3α,5α-THP) are secreted by ovaries, adrenals, and glial cells. 3α,5α-THP in the midbrain ventral tegmental area mediates sexual receptivity of rodents through its actions at GABA A , NMDA, and/ or D 1 receptors. The extent to which 3α,5α-THP may influence anti-anxiety/anti-stress effects, conditioning and/or reward through these substrates and/or by altering hypothalamic pituitary adrenal axis function is discussed. Biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 120 publications
5
90
0
3
Order By: Relevance
“…Oral administration of P 4 has also been reported to have similar effects on men and women [18,73,74]. As well, we have found that cocaine administration enhances corticosterone in rats, and pre-treatment with P 4 can moderately attenuate this [23]. 3α,5α-THP may have effects to reduce reinforcing effects of drugs and this may be due, in part, to its ability to dampen stress reactivity.…”
Section: Discussionsupporting
confidence: 65%
“…Oral administration of P 4 has also been reported to have similar effects on men and women [18,73,74]. As well, we have found that cocaine administration enhances corticosterone in rats, and pre-treatment with P 4 can moderately attenuate this [23]. 3α,5α-THP may have effects to reduce reinforcing effects of drugs and this may be due, in part, to its ability to dampen stress reactivity.…”
Section: Discussionsupporting
confidence: 65%
“…Rats with natural elevations in progestogens have decreased anxiety-and depressive-like behavior and this effect is mimicked by P 4 administration to ovx rats or mice (Frye et al 2000(Frye et al , 2006aFrye and Rhodes 2006;Frye and Walf 2002;MartinezMota et al 1999;Rodriguez-Landa et al 2007). Attenuating metabolism of P 4 to 3α,5α-THP in a 5α-reductase knockout model, or with a 5α-reductase inhibitor administered systemically or to the hippocampus/amygdala, increases anxiety-like and depressive-like behavior in rodents with natural elevations in P 4 or those administered P 4 (Frye andWalf 2002, 2004;Rhodes and Frye 2001;Walf et al 2006). These data, in addition to the present findings that P 4 administration decreased depressive-like behavior in wildtype and APPswe+PSEN1Δ9 mice, suggest that P 4 and its metabolites may have beneficial effects on affective behavior in a healthy as well as a compromised system.…”
Section: Discussionmentioning
confidence: 99%
“…Progestogens are trophic factors with a wide variety of functional effects throughout the lifespan (reviewed in Frye 2007). In the brain, P 4 is converted by the 5α-reductase enzyme to dihydroprogesterone (DHP), which is then converted to 3α,5α-THP by the 3α-hydroxysteroid dehydrogenase enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 3α5α-THP's effects to prolong the opening of GBR chloride channels in vitro can be inhibited with antagonists of G-proteins, protein kinase C (PKC), or cAMP-dependent protein kinase [49]. Further, systemic administration of P 4 increases levels of cAMP in the prefrontal cortex in a 3α5α-THP-and GBR-dependent manner [32][33]50]. Thus, together these data suggest that activity of signal transduction factors may underlie \functioning of progestins at downstream targets, such as GBRs and D 1…”
Section: The Role Of Signal Transduction Cascades For Progestins' Actmentioning
confidence: 99%